Choosing Formulas for Market Access Negotiations: Efficiency and Market Access Considerations - François, Joseph; Martin, Will; Manole, Vlad (World Bank, Washington, DC, 2012)
An important issue in multilateral trade negotiations is the approach taken to reduce tariffs. The authors believe that there are important advantages in formula approaches and survey a range of options between the sharply top-down Swiss formula and proportional cuts in tariffs. Over the range the authors consider, they find that the economic efficiency impacts for the importer are not greatly influenced by the extent to which higher tariffs face bigger cuts. However, top-down approaches appear to be more effective in reducing tariff escalation, and provide greater market access gains to poor countries.